(untitled) (Applied Biological Research, 2024)
Suaeda maritima (L.) Dumort., an annual halophyte herb under the family Chenopodiaceae, grows gregariously along the south-east coast of India. This salt marsh species is regularly used by the local people as food as well as for curing many diseases. Earlier works reported the presence of phenotypic plasticity as well as morpho-anatomical variations amongst the individuals of the species. Cytological studies were undertaken to characterize the individuals of the species with respect to the karyotype. The diploid chromosome number of S. maritima was determined as 2n=18 from the root tips of the species. The average length of metaphase chromosomes was 0.74±0.16 μm (micrometre) with the total haploid chromosome length was 6.68 ±0.28 μm. The average arm ratio was 1.13 ±0.14 with the average centromeric index as 0.46 ±0.12. All the 9 pairs of chromosomes were metacentric and out of 18 chromosomes 4 chromosomes contained NOR. The values of the symmetry index (S%) and the degree of karyotype asymmetry (A) was noted 51.51 ±3.05 and 0.05 ±0.01 respectively. Intra-chromosomal asymmetry index (A1) and inter-chromosomal asymmetry index (A2) were 0.10 ±0.02 and 0.22 ±0.02 respectively.